If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-2 + 2v + 2u)(-7) = 0 Reorder the terms: (-2 + 2u + 2v)(-7) = 0 Reorder the terms for easier multiplication: -7(-2 + 2u + 2v) = 0 (-2 * -7 + 2u * -7 + 2v * -7) = 0 (14 + -14u + -14v) = 0 Solving 14 + -14u + -14v = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14u + -14 + -14v = 0 + -14 Reorder the terms: 14 + -14 + -14u + -14v = 0 + -14 Combine like terms: 14 + -14 = 0 0 + -14u + -14v = 0 + -14 -14u + -14v = 0 + -14 Combine like terms: 0 + -14 = -14 -14u + -14v = -14 Add '14v' to each side of the equation. -14u + -14v + 14v = -14 + 14v Combine like terms: -14v + 14v = 0 -14u + 0 = -14 + 14v -14u = -14 + 14v Divide each side by '-14'. u = 1 + -1v Simplifying u = 1 + -1v
| -2*x+9=25 | | -2(r-6)=-37 | | 2*x+7=5 | | (y-15)-(1y-10)=19 | | 3(2x-5)-4(x-1)=(-3x-6)-3(x+3) | | 5*x+3=13 | | -9x-24=-11x+10 | | -6t=-39 | | log(x+15)-log(x)=0.65 | | 40x=18000+5y | | -47-91=156-9x | | -32-4x=46-x | | 2x-5=5-2 | | 5x-3(2x-10)=25 | | 34+03*2-25+5= | | z^2-(3+4i)z-1-5i=0 | | -46-(-28)= | | 78+n=3n-40 | | 5y-8=12x+4 | | 5y+24=y-8 | | 1.84g-8=0.28 | | 48=3.2x | | 4x+8-8x=32-4x | | 84+n=36-3n | | 3y-18=6 | | 7-1.5x=62.5 | | 4x-47=7x+22 | | 5+5+5+5+5=555 | | 7-1.5x=64 | | 4x-2x=7+13 | | 4a+3=3a+13 | | -6a+(-18)= |